Fabrication and characterization of hydroxyapatite / poly(lactic-co-glycolic) acid composite as scaffold in bone tissue engineering - Basali, Arriane Gayle B.; Leron, Angela Marie S.; Rodgers, Joelle S.
Bone fractures and injuries are usually treated through the use of bone grafting or through the use of synthetic bone replacements. However, the use of such replacements gives rise to various problems that include donor scarcity, supply limitation, pathogen transfer, biocompatibility issues and limited functional recovery. To overcome these problems, bone tissue engineering approaches are emerging as convenient alternatives to promote the regenerative ability of the bone rather that replacing it entirely. In this study, a biomaterial made up of polymer and ceramic was fabricated as a bone scaffold which has the ability to degrade overtime to accommodate the regeneration of natural bone cells and tissues. Poly (lactic-co-glycolic) acid or PLGA and hydroxyapatite (HA) were synthesized via polycondensation and extracted from porcine bones respectively. These two materials were then used to fabricate a biocomposite employing a simple dissolution method. Two PLGA with varying lactide to glycolide ratio of 50:50 and 75:25 were synthesized. Four treatment combinations, which have varying lactide to glycolide ratio and HA filler concentrations were used and characterized via Fourier transform infrared spectroscopy (FTIR), in vitro degradation in a simulated body fluid, and surface energy analysis through contact angle measurements. The FTIR spectra have shown a successful fabrication of the individual components through a simple process of continuous stirring of lactic and glycolic acid at elevated temperatures for the PLGA and extraction of hydroxyapatite from porcine bones through calcinations in a furnace. Significant degradation was observed for all of the composites subjected to a phosphate buffered solution in a span of one week. Furthermore, it was found out that increasing amounts of glycolide content hastens the degradation behaviour. Results from contact angle measurements also demonstrate the good wettability of the composites implying hydrophilicity and therefore good adhesion of bone cells and tissues onto the scaffold. Increasing the glycolide content also increases the wettability.